Triboelectric nanogenerator based on lignocellulosic waste fruit shell tribopositive material: Comparative analysis. (June 2022) - Saqib, Q.M.; Chougale, M.Y.; Khan, M.U.; Shaukat, R.A.; Kim, J.; Bhat, K.S.; Bae, J.
Abstract: Reusing abundant waste fruit shell (WFS), non-toxic and valueless biomaterial, is urgently needed for waste management and sustainable green environment. This paper demonstrates a rigorous analysis of triboelectric nanogenerator (TENG) based on the various WFS employed as tribopositive materials. WFS possesses different concentrations of lignin and cellulose. Plentiful oxygen containing functional groups in these natural polymers endow high electron-donating capability, resulting in promising potential toward strong tribopositive functionalities. Here, lignocellulose WFS of almond (A), walnut (W), and pistachio (Pi) are explored as tribopositive materials in TENG. A-WFS contains ∼38.47% cellulose with oxygen concentration of 23.3%, while W-WFS carries ∼36.38% cellulose with 25.4% oxygen. On the other hand, the Pi-WFS carries higher cellulose concentration of 43.08% having maximum oxygen concentration of 33.7%. The higher cellulose concentration and oxygen components in Pi-WFS tribopositive layer endows the TENG device to yield the highest open-circuit voltage, short circuit current, and maximum power density of 700 V, 95 μA, and 416.14 μWcm −2, respectively. Moreover, WFS-based TENG devices are further employed to charge commercial capacitors and powering LEDs, stopwatch, and electronic calculator. These results ensure the unique functionalities of WFS to generate electrical energy for environmentally friendly, highly efficient, cost-effective, and sustainable energy harnessing systems. Graphical abstract: Image 1